CODE SWITCHING AND ITS VARIATIONS IN DIGITAL DISCOURSE: A STUDY OF CODE SWITCHING TYPES IN THE MATA NAJWA PODCAST WITH RETNO MARSUDI AND SRI MULYANI - Mariana Mariana; Rudi Purwana; Ani Deswita Chaniago; Laila Hasyim; Horia Siregar (Journal Analytica Islamica, 2025)
The phenomenon of code-switching has become an increasingly significant linguistic practice in digital communication, especially within public discourse featuring influential figures. This study aims to analyze the types, functions, and socio-pragmatic meanings of code-switching in the Mata Najwa podcast episode titled Women in Power, featuring Indonesia's key female leaders Retno Marsudi and Sri Mulyani. Using a qualitative case study design and grounded in sociolinguistic theory, this research investigates how code-switching operates as a communicative strategy for constructing identity, negotiating power, and representing leadership in digital spaces. Data were collected through non-participant observation, verbatim transcription, and visual documentation. Thematic analysis was conducted using Hoffman's (1991) typology of code-switching, comprising inter-sentential, intra-sentential, and tag-switching. Findings indicate that intra-sentential switching is most dominant (59%), followed by inter-sentential (30%) and tag-switching (11%). The results reveal that code-switching functions not only as a bilingual communication tool but also as a rhetorical and symbolic act that reflects pragmatic competence, global orientation, and cultural identity alignment. This linguistic behavior signifies how female leaders articulate global authority while maintaining local identity, demonstrating code-switching as a form of gendered communicative performance. The study contributes to digital sociolinguistics and gender communication studies by offering empirical evidence of how multilingual discourse in podcasts mediates identity, power, and leadership narratives in contemporary digital culture.